Structural aspects of the zygotic embryogenesis of Acca sellowiana (O. Berg) Burret (Myrtaceae) - Pescador,Rosete (2009)
Acca sellowiana has anatropous, bitegmic and crassinucellate ovules. The outer and inner integuments are double-layered except in the micropyle, where they are composed of more layers; the micropyle is zig-zag shaped. The egg apparatus lies at the micropylar pole, and the zynergids present a conspicuous filiform apparatus. The antipodal cells are present in the chalazal region, persisting before the occurrence of double fertilization. The zygote is visible 21 days after pollination; nuclear endosperm is already present. The first mitotic division of the zygote occurs at 24th day. The globular, cordiform and torpedo embryo stages can be seen at 30, 45 and 60 days after pollination, respectively. The mature embryo characterized by the presence of a well-developed hypocotyl-radicular axis with two fleshy and folded cotyledons was observed 120 days after pollination. Endosperm is absent in the seeds, and the embryo has spiral form, characteristic of Myrtinae. The zygotic embryology studies of A. sellowiana indicate that this species has embryological characteristics which are in agreement with those reported for Myrtaceae (Myrteae, Myrtinae), and also broaden the knowledge about the sexual reproduction of this native species, whose commercial cultivation has been growing.